2011
DOI: 10.1093/pcp/pcr105
|View full text |Cite
|
Sign up to set email alerts
|

RSOsPR10 Expression in Response to Environmental Stresses is Regulated Antagonistically by Jasmonate/Ethylene and Salicylic Acid Signaling Pathways in Rice Roots

Abstract: Plant roots play important roles not only in the absorption of water and nutrients, but also in stress tolerance. Previously, we identified RSOsPR10 as a root-specific pathogenesis-related (PR) protein induced by drought and salt treatments in rice. Transcripts and proteins of RSOsPR10 were strongly induced by jasmonate (JA) and the ethylene (ET) precursor 1-aminocyclopropane-1-carboxylic acid (ACC), while salicylic acid (SA) almost completely suppressed these inductions. Immunohistochemical analyses showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(101 citation statements)
references
References 48 publications
2
99
0
Order By: Relevance
“…The link between this modulation and the RSS3-mediated regulation of JA-responsive genes remains unclear, although JAs are known to be involved in various stress responses (Wasternack, 2007;Takeuchi et al, 2011). Notably, Arabidopsis MYC2 was originally identified as a transcriptional activator of stress-responsive genes (Abe et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between this modulation and the RSS3-mediated regulation of JA-responsive genes remains unclear, although JAs are known to be involved in various stress responses (Wasternack, 2007;Takeuchi et al, 2011). Notably, Arabidopsis MYC2 was originally identified as a transcriptional activator of stress-responsive genes (Abe et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…JAs are also involved in the responses to a variety of abiotic stresses, such as salinity and drought stress (Wasternack, 2007;Takeuchi et al 2011). In cultured Arabidopsis thaliana cells, JAs mediate the transcriptional reprogramming of genes, as reflected in the repression of the cell cycle and the biosynthesis of phenylpropanoids, including lignin precursors (Pauwels et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulations of JIOPR10 [73] and OsPR10 [74] transcripts were observed on application of JA and SA in rice leaves. The folding canon of PR-10 proteins is found in the ABA receptor family known as PYR/PYL/RCAR (pyrabactin resistance/PYR-like/regulatory component of ABA response) [21].…”
Section: Signaling Nodes: Pr-10 In Response To Signaling Pathwaysmentioning
confidence: 97%
“…Subsequent studies revealed the involvement of the JA/ET signaling pathway in RSOsPR10 induction during responses to high salinity conditions and wounding, and the inhibition of expression by exogenous salicylic acid treatment (Takeuchi et al 2011). Immunohistochemical analyses indicated RSOsPR10 accumulated mainly in root cortical cells after stress exposure and treatments with JA and ET, suggesting it affects root growth in response to environmental stresses.…”
Section: Introductionmentioning
confidence: 99%